Association of higher bone turnover with risk of curve progression in adolescent idiopathic scoliosis - Zhang, Jiajun; Wang, Yujia; Cheng, Ka-lo; Cheuk, Kayee; Lam, Tsz-ping; Hung, Alec L.H.; Cheng, Jack C.Y.; Qiu, Yong; Müller, Ralph; Christen, Patrik; Lee, Wayne Y.W. (Bone (New York, N.Y.), 2021)
Emerging evidence suggest abnormal bone metabolism and defective bone qualities are associated to etipathogenesis of Adolescent Idiopathic Scoliosis (AIS). Systemic low bone mass is important prognosticator to predict risk of curve progression in AIS. The underlying mechanism is still unclear. We hypothesize that aberrant bone turnover correlates with bone qualities in AIS and associates to risk of curve progression. Two cohorts were included in this study. The case-control study recruited 161 AIS girls and 161 ethnic/age-matched healthy girls. The longitudinal cohort recruited 128 AIS girls with two-year follow-up. Areal bone mineral density (BMD) at femoral necks were measured with dual-energy x-ray absorptiometry (DXA), and bone qualities of distal radius by high-resolution peripheral quantitative computed tomography (HR-pQCT). Time-lapse analysis of registered HR-pQCT images estimated local bone remodeling quantitatively. Serum levels of CTX and P1NP were measured with ELISA kits. AIS presented significantly higher serum level of P1NP. In both AIS and control, the negative correlations were consistently observed between serum CTX/P1NP levels and most cortical bone quality parameters after adjustment to age. Significant correlation between serum bone turnover markers and trabecular bone parameters have been observed only in control. Progressive AIS has significant increase of serum P1NP level at first clinic visit. Time lapse register analysis showed high bone resorption and low net bone gain was associated with risk of progression in AIS. Our study characterized AIS with higher serum bone turnover markers, which may contribute to defective bone qualities in AIS. For the first time, we showed that progressive AIS had higher systemic bone turnover markers level and local bone remodeling. This fresh evidence indicated association between disrupted bone turnover and risk of progression of AIS, which set the foundation of new prognostic method and of novel treatment target to curve progression. This study demonstrated the importance of bone metabolism in developing disease management of AIS to achieve goal of early prediction and non-surgical modulation. •Patients with AIS have higher serum levels of P1NP and CTX than control.•Risk of curve progression is associated with higher serum level of P1NP.•Time-lapse HR-pQCT analysis reveals higher bone turnover in progressive AIS.•Bone turnover could be novel clinical prognostic factor for AIS.